2020
DOI: 10.1093/mnras/staa747
|View full text |Cite
|
Sign up to set email alerts
|

The White Dwarf Binary Pathways Survey −III. Contamination from hierarchical triples containing a white dwarf

Abstract: The White Dwarf Binary Pathways Survey aims at increasing the number of known detached A, F, G and K main sequence stars in close orbits with white dwarf companions (WD+AFGK binaries) to refine our understanding about compact binary evolution and the nature of Supernova Ia progenitors. These close WD+AFGK binary stars are expected to form through common envelope evolution, in which tidal forces tend to circularize the orbit. However, some of the identified WD+AFGK binary candidates show eccentric orbits, indic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 61 publications
1
11
0
Order By: Relevance
“…Following this strategy, we have so far identified the first presupersoft X-ray binary system (Parsons et al 2015), confirmed that our target selection is reliable and in virtually all cases the UV excess is indeed indicative of a white dwarf (Parsons et al 2016), published the first results of our radial velocity campaign (Rebassa-Mansergas et al 2017), estimated the limited contamination from triple systems motivated by the discovery of the first hierarchical triple system in the survey (Lagos et al 2020), and identified and characterised 26 new close WD+AFGK systems (Ren et al 2020) through radial velocity variations. Most importantly for this work, we measured the periods of six systems and found all of them to be PCEBs with periods below 2.5 days and circular orbits.…”
Section: Introductionsupporting
confidence: 64%
See 4 more Smart Citations
“…Following this strategy, we have so far identified the first presupersoft X-ray binary system (Parsons et al 2015), confirmed that our target selection is reliable and in virtually all cases the UV excess is indeed indicative of a white dwarf (Parsons et al 2016), published the first results of our radial velocity campaign (Rebassa-Mansergas et al 2017), estimated the limited contamination from triple systems motivated by the discovery of the first hierarchical triple system in the survey (Lagos et al 2020), and identified and characterised 26 new close WD+AFGK systems (Ren et al 2020) through radial velocity variations. Most importantly for this work, we measured the periods of six systems and found all of them to be PCEBs with periods below 2.5 days and circular orbits.…”
Section: Introductionsupporting
confidence: 64%
“…These systems can easily be interpreted as PCEBs. At somewhat longer orbital periods (weeks), we have so far not yet identified a single PCEB but instead four systems, three in this work and one in Lagos et al (2020), with eccentric orbits, which are most likely main sequence binaries or the inner binaries of hierarchical triple systems, either with no white dwarf at all or with the white dwarf being the distant tertiary companion candidate. In what follows we discuss the implications of this finding for our survey as well as for our understanding of white dwarf binary star formation.…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations